Matrix Metalloproteinases and Tissue Inhibitors of Metalloproteinases Are Potential Biomarkers of Pulmonary and Extra-Pulmonary Tuberculosis - Kathamuthu, Gokul Raj; Kumar, Nathella Pavan; Moideen, Kadar; Nair, Dina; Banurekha, Vaithilingam V.; Sridhar, Rathinam; Baskaran, Dhanaraj; Babu, Subash (Frontiers in Immunology, 2020)
Matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinase (TIMPs) are potential regulators of tuberculosis (TB) pathology. Whether they are candidates for non-sputum-based biomarkers for pulmonary TB (PTB) and extra-pulmonary TB (EPTB) is not fully understood. Hence, to examine the association of MMPs and TIMPs with PTB and EPTB, we have measured the circulating levels of MMPs (MMP-1, 2, 3, 7, 8, 9, 12 and 13) and TIMPs (TIMP-1, 2, 3 and 4) in PTB, EPTB and compared them with latent tuberculosis (LTB) or healthy control (HC) individuals. We have also assessed their circulating levels before and after the completion of anti-tuberculosis treatment (ATT). Our data describes that systemic levels of MMP-1, 8, 9, 12 were significantly increased in PTB compared to EPTB, LTB and HC individuals. In contrast, MMP-7 was significantly reduced in PTB compared to EPTB individuals. Likewise, the systemic levels of MMP-1, 7, 13 were significantly increased in EPTB in comparison to LTB and HC individuals. In contrast, MMP-8 was significantly reduced in EPTB individuals compared to LTB and HC individuals. In addition, the systemic levels of TIMP-1, 2, 3 were significantly diminished and TIMP-4 levels were significantly enhanced in PTB compared to EPTB, LTB and HC individuals. The circulating levels of TIMP-2 was significantly reduced and TIMP-3 was significantly elevated in EPTB individuals in comparison with LTB and HCs. Some of the MMPs (7, 8, 9, 12, 13 in PTB and 1, 7, 8, 9 in EPTB) and TIMPs (1, 2, 3, 4 in PTB and 4 in EPTB) were significantly modulated upon treatment completion. ROC analysis showed that MMP-1, 9 and TIMP-2, 4 could clearly discriminate PTB from EPTB, LTB and HCs and MMP-13 and TIMP-2 could clearly discriminate EPTB from LTB and HCs. Additionally, multivariate analysis also indicated that these alterations were independent of age and sex in PTB and EPTB individuals. Therefore, our data demonstrates that MMPs and TIMPs are potential candidates for non-sputum-based biomarkers for differentiating PTB and EPTB from LTB and HC individuals.